2022
DOI: 10.1093/plphys/kiac127
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress leads to rapid lipid remodeling and transcriptional adaptations in Nicotiana tabacum pollen tubes

Abstract: After reaching the stigma, pollen grains germinate and form a pollen tube that transports the sperm cells to the ovule. Due to selection pressure between pollen tubes, pollen grains likely evolved mechanisms to quickly adapt to temperature changes to sustain elongation at the highest possible rate. We investigated these adaptions in tobacco (Nicotiana tabacum) pollen tubes grown in vitro under 22 °C and 37 °C by a multi-omics approach including lipidomic, metabolomic, and transcriptomic analysis. Both glycerop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 111 publications
1
15
1
Order By: Relevance
“…Paradoxically, this is often the case when pollen tubes are separated from the medium without great care prior to hot isopropanol treatment. Seeming PA levels in whole cell samples may reach 20-60% of total glycerolipids, as was reported for soybean, tobacco, or Arabidopsis pollen (Djanaguiraman et al, 2013;McDowell et al, 2013;Krawczyk et al, 2022). Our data, reporting whole cell PA levels at 1.5-2.3% of total glycerolipids and PA levels in the PM at ~7% of total glycerolipids, agree with the data on wheat pollen and purified plasma membrane from tobacco cell culture (Cacas et al, 2016;Narayanan et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Paradoxically, this is often the case when pollen tubes are separated from the medium without great care prior to hot isopropanol treatment. Seeming PA levels in whole cell samples may reach 20-60% of total glycerolipids, as was reported for soybean, tobacco, or Arabidopsis pollen (Djanaguiraman et al, 2013;McDowell et al, 2013;Krawczyk et al, 2022). Our data, reporting whole cell PA levels at 1.5-2.3% of total glycerolipids and PA levels in the PM at ~7% of total glycerolipids, agree with the data on wheat pollen and purified plasma membrane from tobacco cell culture (Cacas et al, 2016;Narayanan et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, PS molecular species show distinct trends in both acyl-chain composition and relative changes during pollen germination and growth, which are unapparelled with other tested glycerolipids ( Figure 3 ). First, predominant PS species PS 40:2, PS 40:3, PS 42:2, and PS 42:3, containing very-long-chain fatty acids (VLCFAs), together constitute >90% of total pollen PS, which contrasts with reported values for Arabidopsis ( McDowell et al., 2013 ), wheat ( Narayanan et al., 2018 ) and tobacco ( Krawczyk et al., 2022 ) pollen. Second, PS species show unique dual dynamics, where particularly shorter species (PS 34:3 and 34:2) are significantly upregulated in the pollen tube phase.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In land plants lipid droplet (LD) formation and TAG accumulation is common to many stress responses, including heat, cold and drought (Higashi et al, 2015; Mueller et al, 2015; Gidda et al, 2016; Doner et al, 2021; Krawczyk et al, 2022). We observed that cells of Mesotaenium accumulated inclusions resembling LDs (Figure 6a) upon prolonged exposure to stress.…”
Section: Resultsmentioning
confidence: 99%
“…It has been known that low or high temperature mostly have opposite impacts on PP (Krawczyk et al, 2022). For instance; PG and PT length were decreased by hightemperature treatment at 30 °C in hazelnut (Çetinbaş-Genç et al, 2019) and, decreased by high-temperature treatment above 35 °C in cotton and tobacco (Song et al, 2015;Parrotta et al, 2016).…”
Section: Discussionmentioning
confidence: 99%